2018
DOI: 10.1097/md.0000000000010889
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram criteria of limb leads predicting right coronary artery as culprit artery in inferior wall myocardial infarction

Abstract: Background:Prior studies have proposed several electrocardiogram (ECG) criteria in limb leads for identifying the culprit coronary artery (CCA) in patients with acute inferior wall myocardial infarction (IWMI). The aim of our study was to conduct an evidence-based evaluation and test accuracy comparison of these criteria.Methods:We searched the PubMed, Embase, and Ovid. Eligible studies to assess the diagnostic performance of ECG criteria predicting CCA in IWMI were reviewed for inclusion. A diagnostic meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In general, acute transmural inferior MI will show signs (ST-elevation) in leads II, III, and aVF. ST-segment elevation in lead III greater than II is predictive of RCA occlusion, as demonstrated by this patient [4]. It is important to identify the occluded artery to guide decisions on emergent treatment as well as PCI, considering that it is not recommended to perform PCI on uninvolved arteries [4].…”
Section: Discussionmentioning
confidence: 81%
“…In general, acute transmural inferior MI will show signs (ST-elevation) in leads II, III, and aVF. ST-segment elevation in lead III greater than II is predictive of RCA occlusion, as demonstrated by this patient [4]. It is important to identify the occluded artery to guide decisions on emergent treatment as well as PCI, considering that it is not recommended to perform PCI on uninvolved arteries [4].…”
Section: Discussionmentioning
confidence: 81%
“…Previous reports [11][12][13][14][15]18,[23][24], more frequently used ST-segment elevation in lead III than lead II (or lead III > II) as an indicator of infarct-related coronary artery at the RCA. One recent meta-analysis also demonstrated that ST segment elevation in lead III > II provided better prediction of right coronary artery as the culprit artery in inferior myocardial infarction [28].…”
Section: Discussionmentioning
confidence: 97%
“…Using lead III>II is an ideal algorithm to identify RCA culprit lesions as evidenced by a recent large meta-analysis. 8 This can then be augmented by additional criteria such as reciprocal ST depression in aVL and lead I to improve specificity, as a number of studies have shown. 8 …”
Section: Discussionmentioning
confidence: 99%
“… 8 This can then be augmented by additional criteria such as reciprocal ST depression in aVL and lead I to improve specificity, as a number of studies have shown. 8 …”
Section: Discussionmentioning
confidence: 99%